Junk foods wars - Jude, Erica; Video Education Australia (Bendigo, Vic. : Video Education Australia, 2005)
This high-energy video shows how to defend against the dangers of junk food. Straightforward discussions and dramatizations arm students with a wealth of information on the updated 2005 food pyramid, how to read ingredient labels, and more
DVD format
Keywords: Junk food; Convenience foods; Children -- Nutrition